Synthesis, Docking Studies and Pharmacological Evaluation of Serotoninergic Ligands Containing a 5-Norbornene-2-Carboxamide Nucleus - Rosa Sparaco; Ewa Kędzierska; Agnieszka A. Kaczor; Anna Bielenica; Elisa Magli; Beatrice Severino; Angela Corvino; Ewa Gibuła-Tarłowska; Jolanta H. Kotlińska; Giorgia Andreozzi; Paolo Luciano; Elisa Perissutti; et al. (Molecules, 2022)
A new series of 5-norbornene-2-carboxamide derivatives was prepared and their affinities to the 5-HT1A, 5-HT2A, and 5-HT2C receptors were evaluated and compared to a previously synthesized series of derivatives characterized by exo-N-hydroxy-5-norbornene-2,3-dicarboximidenucleus, in order to identify selective ligands for the above-mentioned subtype receptors. Arylpiperazines represents one of the most important classes of 5-HT1AR ligands, and recent research concerning new derivatives has been focused on the modification of one or more portions of such pharmacophore. The combination of structural elements (heterocyclic nucleus, propyl chain and 4-substituted piperazine), known to be critical to the affinity to 5-HT1A receptors, and the proper selection of substituents led to compounds with high specificity and affinity towards serotoninergic receptors. The most active compounds were selected for further in vivo assays to determine their functional activity. Finally, to rationalize the obtained results, molecular docking studies were performed. The results of the pharmacological studies showed that Norbo-4 and Norbo-18 were the most active and promising derivatives for the serotonin receptor considered in this study.